Descriptive Analysis of Resources Used to Learn About Residency Programs Since Transition to Virtual Interviews - Richard Bounds; John Priester; Benjamin Lewis; Roz King; Skyler Lentz (Western Journal of Emergency Medicine)
Introduction: The transition to virtual interviews over the past four years has been associated with changes to the ways that applicants collect information on residency programs. Methods: Our program collected free-response data from questionnaires completed by applicants prior to their virtual interview days over the course of four recruitment cycles. We performed a descriptive analysis of these responses to identify the frequency with which students have been accessing various resources to learn about programs, and to learn how that has changed over time. Results: Our findings over four years and 322 applicants (of 391 surveyed, response rate 82%) indicated that the three most common sources of information were individual program websites, the Emergency Medicine Resident’s Association (EMRA) Match website, and Instagram. These sources were reported more frequently than personal experience, word of mouth, and advice from mentors. Other online resources were rarely used. Conclusion: These findings may help program leaders to direct their limited time and attention towards marketing their programs through online resources most commonly used by applicants.